An Inverse Problem for the Absorption of Fatty Acid. Issue 1 (March 2015) - Hai, Y.; Kokulan, N.; Lai, C.-H.; George, E.; Pericleous, K.A.
The mathematical model of fatty acid kinetics in plasma is considered. The model is based on physiological knowledge and constructed by means of experimental data. In order to estimate the unknown parameters in the model, methods of inverse problems are used with measurements and ordinary differential equations governing the kinetics. Different sets of experimental data were used to establish the unknown parameters in the mathematical model. This enables one to understand the absorption process of nutrients and provide a computational estimation for the absorption rate.